Report of Scientific and Standardization Subcommittee on Neonatal Hemostasis Diagnosis and Treatment of Neonatal Thrombosis - Schmidt, Barbara; Andrew, Maureen (Thrombosis and Haemostasis, 1992)
Thrombotic disease in newborn infants is common and serious enough to require effective and safe intervention (1). Flowever, neonatal thrombosis is also sufficiently rare to prompt anecdotal observations rather than controlled clinical trials. While there is an abundance of case reports in the pediatric literature, there is a conspicuous paucity of well-designed studies to guide clinical decision-making (2).The Subcommittee on Neonatal Hemostasis of the Scientific and Standardization Committee recognizes the need for multicenter controlled clinical trials to determine the risks and benefits of different treatment modalities for neonatal thrombosis. Until such data becomes available, the following recommendations may assist clinicians in the management of newborn infants with thrombotic disease. These recommendations were endorsed by the Subcommittee after careful review of the literature and several consensus meetings.